Makna Tuturan Mowindahako (Pelamaran) Suku Moronene di Desa Tontonuhu Kecamatan Kontununu Kabupaten Bombana - Wilda Wilda; La Niampe; Rahmat Sewa Suraya (LISANI: Jurnal Kelisanan, Sastra, dan Budaya, 2024)
This study aims to determine and describe the meaning of speech in the Mowindahako (proposal) stages of Moronene tribal marriage in Tontonunu Village, Tontonunu District, Bombana Regency. This study uses a qualitative research type, namely research whose procedures produce descriptive data in the form of written or spoken words from traditional leaders (Tolea). Data collection techniques in the study used observation, interview, and documentation methods. The research analysis used a qualitative descriptive method. The results of the study show that the meaning of the Mowindahako (proposal) tradition speech of the Moronene tribe in Tontonunu Village can be seen in several stages, namely: the Kohala stage, the first Mowindahako (Proposal) stage, the second Mowindahako (Proposal) stage, the Moduduhi stage, and the Mompokontodo stage.